PENGARUH PENGGUNAAN TEPUNG LIMBAH WORTEL (Daucus Carrota L) DALAM RANSUM TERHADAP EFISISENSI PENGGUNAAN PROTEIN DAN KALSIUM AYAM BROILER. (Effect of Use of Waste Product of Carrot (Daucus carota. L) Meal in the Diet to Effiency Use Protein and Calcium Broiler Chicken) - T. j. Prasetyo; v. D. Yunianto; L. D. Mahfudz (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2018)
The aim of this experiment was to determined the use of waste product of carrot (Daucus carota. L) meal in the ration of broiler on protein consumption, protein efficiency ratio, calcium retention, and body weight gain. The materials were 144 broiler chickens was used as material animal with an average body weight 181,40 ± 11,31 g at 7 days old. This study used a completely randomized design (CRD) with 4 treatments and 6 replications and each reserch unit consisted of 6 chickens. The treatments diets were T0 (0 % Carrot meal), T1 (2% Carrot meal), T2 (4% Carrot meal), and T3 (6% Carrot meal). The data were processed using analysis of variance with F test. The results showed that utilization waste product of carrot meal up to 6% in the diet resulted did not affected to protein consumption and protein efficiency ratio, while could improve calcium retention. Conclusion waste product of carrot meal can be used as feed stuff of broiler chicken.